2023
DOI: 10.1021/acs.langmuir.3c01227
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of WO3-Based Photochromism in Polyvinyl Alcohol Film

Abstract: Tungsten oxide (WO 3 ) has been extensively studied for various photochromic applications. Blue coloration of WO 3 is explained in terms of the intervalence charge transfer (IVCT) transition of electrons between W 6+ and W 5+ . However, various absorption spectra with different shapes have been reported. Herein, a transparent film was prepared by drying aqueous solutions containing polyvinyl alcohol, WO 3 nanoparticles and ethylene glycol (EG). For comparison, the photochromic behavior of an aqueous WO 3 collo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Based on several literatures on WO 3 photochromism and the results obtained in this study, we propose the relationship between the adsorption behavior of Phe molecules on the WO 3 surface and the photochromic behavior of WO 3 nanocolloid particles in the acidic Phe/TMβCDx/WO 3 ternary aqueous system, as shown in Scheme . In the bulk aqueous solution, cationic Phe molecules form inclusion complexes with TMβCDxs with 1:1 stoichiometric ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Based on several literatures on WO 3 photochromism and the results obtained in this study, we propose the relationship between the adsorption behavior of Phe molecules on the WO 3 surface and the photochromic behavior of WO 3 nanocolloid particles in the acidic Phe/TMβCDx/WO 3 ternary aqueous system, as shown in Scheme . In the bulk aqueous solution, cationic Phe molecules form inclusion complexes with TMβCDxs with 1:1 stoichiometric ratio.…”
Section: Resultsmentioning
confidence: 99%
“…58,59 Recent work has suggested that the absorption stems from intervalence charge transfer of mixed-valent W− O−W pairs (e.g., W 5+ −O−W 6+ ). 60,61 Deconvolution of this absorbance is suggestive of the presence of predominantly W 5+ species after this step (Figure S15), though the relative cross sections of these two absorption bands have not been reported, preventing quantification of the two species through UV−vis spectroscopy. The second oxidation step eliminates this feature, and the sample absorption spectrum becomes essentially identical to the initial spectrum assigned to W 6+ , highlighting the reversibility of oxidation state changes for W in this catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%